Perovskite solar cell and integrated sealing and welding method thereof
Patent Information
- Application Number
- CN202611129161.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-16
AI Technical Summary
分步式连接与封装工艺,电极连接与封装保护通常分开进行,工序较多,界面暴露时间长,易引入位置偏移、应力集中及封装一致性差等问题
1、本发明通过在银箔表面预镀焊料层制得焊带,结合层压工艺,在较低温度下完成电极互连,有效规避200℃以上高温焊接对钙钛矿活性层、载流子传输层及界面接触层的热损伤,保障电池片光电性能。此外采用高温布、封装覆盖层、封装胶膜层、焊带及电池片的特定叠层顺序,并配合带有凹槽和限位槽的治具,实现焊带精准定位,防止封装过程中的位置偏移与应力集中,提升电极引出精度和结构均匀性,再者,配合层压一次性完成电极连接与封装保护,显著缩短界面暴露时间,减少工序周转。
Smart Images

Figure CN122935121A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of photovoltaic cell technology, and in particular to a perovskite solar cell and its integrated sealing method. Background Technology
[0002] Perovskite solar cells possess high photoelectric conversion efficiency, simple fabrication process, high material utilization, and low-cost manufacturing potential. However, perovskite materials and their interface layers are typically sensitive to temperature, humidity, oxygen, and mechanical stress, leading to performance degradation during cell encapsulation and interconnection, thus limiting their practical applications.
[0003] The electrode lead-out and encapsulation of existing perovskite solar cells typically employ the following methods: Traditional soldering, such as Sn-Pb and Sn-Ag-Cu systems, typically involves soldering temperatures above 200℃, which can easily cause thermal damage to the perovskite active layer, carrier transport layer, and interface contact layer, leading to a decline in cell performance. While conductive adhesive bonding can lower the bonding temperature, its interfacial conductivity stability, long-term reliability, and environmental adaptability are usually insufficient, making it prone to increased contact resistance, interface aging, and connection failure during long-term use. Step-by-step bonding and encapsulation processes, where electrode bonding and encapsulation protection are usually performed separately, involve numerous steps, prolonged interface exposure time, and are prone to problems such as positional misalignment, stress concentration, and poor encapsulation consistency.
[0004] Therefore, there is an urgent need to develop an integrated technology solution that can complete electrode interconnection and cell encapsulation at lower temperatures to reduce thermal damage, simplify the process flow, and improve the encapsulation reliability and long-term stability of perovskite solar cells. Summary of the Invention
[0005] Based on the above analysis, the present invention aims to provide a perovskite solar cell and its integrated sealing method, which simultaneously achieves interconnection and encapsulation, reduces the degradation of photoelectric performance after encapsulation, and improves long-term reliability.
[0006] On one hand, the present invention provides an integrated sealing method for perovskite solar cells, comprising the following steps: S1: A solder layer is pre-plated on the surface of silver foil to obtain solder ribbon; S2: The high-temperature cloth, encapsulation cover layer, encapsulation film layer, positive electrode solder ribbon, battery cell, negative electrode solder ribbon, encapsulation film layer, encapsulation cover layer and high-temperature cloth are stacked and assembled in sequence to form an encapsulation structure. S3: Place the packaging structure in a fixture, the fixture including a body, the body having a groove for accommodating the packaging structure, and the body having a limiting groove for inserting the solder strip, the limiting groove communicating with the groove; S4: Place the fixture in the laminator, adjust the lamination parameters and encapsulate to obtain perovskite solar cell wafers.
[0007] Furthermore, the thickness of the solder layer is 500~1000nm; the thickness of the silver foil is 20~50μm.
[0008] Furthermore, the raw material for preparing the solder layer is Sn-Bi-based solder.
[0009] Furthermore, in the Sn-Bi-based solder, the mass percentage of Sn is 30-60 wt%, and the mass percentage of Bi is 40-70 wt%.
[0010] Furthermore, the Sn-Bi-based solder also contains a modifying element, which is one or more of Ag, In, Sb, and Cu.
[0011] Furthermore, the amount of the modified element added accounts for 0.1~10 wt% of the Sn-Bi-based solder.
[0012] Furthermore, the height of the fixture is 1~1.5mm greater than the thickness of the packaging structure.
[0013] Furthermore, the lamination parameters include a lamination temperature of 90~100℃ and a lamination pressure of -80~-30kPa.
[0014] Furthermore, the number of positive electrode solder strips is 2-4, and the number of negative electrode solder strips is 2-4.
[0015] On the other hand, the present invention provides a perovskite solar cell, which is prepared by the integrated sealing and bonding method described in the present invention.
[0016] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects: 1. This invention creates solder ribbons by pre-plating a solder layer on the surface of silver foil. Combined with a lamination process, electrode interconnection is completed at a lower temperature, effectively avoiding thermal damage to the perovskite active layer, carrier transport layer, and interface contact layer caused by high-temperature welding above 200°C, thus ensuring the photoelectric performance of the solar cell. Furthermore, a specific stacking sequence of high-temperature cloth, encapsulation cover layer, encapsulation film layer, solder ribbon, and solar cell is employed, along with a fixture with grooves and limiting slots, to achieve precise solder ribbon positioning, preventing positional deviation and stress concentration during the encapsulation process, improving electrode lead-out accuracy and structural uniformity. Moreover, the lamination process completes electrode connection and encapsulation protection in one step, significantly shortening interface exposure time and reducing process turnover.
[0017] 2. By limiting the Sn-Bi-based solder and its composition ratio (30~60 wt% Sn, 40~70 wt% Bi) and controlling the solder layer thickness to 500~1000 nm, this invention effectively reduces the solder melting temperature and avoids thermal damage to the perovskite active layer and interface contact layer caused by high-temperature welding. At the same time, the addition of modifying elements such as Ag, In, Sb, and Cu (0.1~10 wt%) optimizes the solder wettability and interface bonding force, thereby improving the reliability of the connection.
[0018] 3. This invention controls the lamination temperature at 90~100℃ and the lamination pressure at -80~-30kPa, and with the fixture height difference (1~1.5mm), it achieves uniform pressure under low temperature negative pressure conditions, effectively reducing encapsulation voids and stress concentration, avoiding cell cracking, and ensuring that the solder is fully wetted and cured, thereby improving the encapsulation density and the long-term service stability of the module.
[0019] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained from what is particularly pointed out in the description and drawings. Attached Figure Description
[0020] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.
[0021] Figure 1 This is a schematic diagram of the fixture structure; Figure 2 A schematic diagram showing the arrangement of the battery cells and solder ribbons; Figure 3 This is a schematic diagram showing the positions of the battery cells and solder strips in the fixture. Figure 4 This is a schematic diagram of the packaging structure; Figure 5 This is a schematic diagram showing the position of the packaging structure in the fixture; Figure 6 This is a picture of the actual product after 3-layer lamination packaging as a comparison example; Figure label: 1. Body; 11. Groove; 12. Limiting groove; 2. Battery cell; 31. Positive electrode solder ribbon; 32. Negative electrode solder ribbon; 4. Encapsulation film layer; 5. Encapsulation cover layer; 6. High temperature cloth. Detailed Implementation
[0022] The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, which constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.
[0023] Perovskite solar cells are highly efficient, simple to manufacture, and low in cost, but their materials are sensitive to temperature, humidity, oxygen, and stress, and are prone to performance degradation during encapsulation and interconnection. In existing electrode lead-out methods, traditional solders (such as Sn-Pb and Sn-Ag-Cu) require soldering temperatures exceeding 200°C, easily leading to thermal damage; conductive adhesives have low connection temperatures but poor long-term reliability; and step-by-step processes involve many steps and long interface exposures, making them prone to misalignment.
[0024] Therefore, the present invention provides an integrated sealing method for perovskite solar cells, comprising the following steps: S1: A solder layer is pre-plated on the surface of silver foil to obtain solder ribbon; S2: The high-temperature cloth, encapsulation cover layer, encapsulation film layer, positive electrode solder ribbon, battery cell, negative electrode solder ribbon, encapsulation film layer, encapsulation cover layer and high-temperature cloth are stacked and assembled in sequence to form an encapsulation structure. S3: Place the packaging structure in a fixture, the fixture including a body, a groove for accommodating the packaging structure being formed in the body; and a limiting groove for inserting the solder strip being formed on the body, and the limiting groove communicating with the groove; S4: Place the fixture in the laminator, adjust the lamination parameters and encapsulate to obtain perovskite solar cell wafers.
[0025] Compared with existing technologies, this invention creates solder ribbons by pre-plating a solder layer on the surface of silver foil and then performing a lamination process to complete electrode interconnection at a lower temperature. This effectively avoids thermal damage to the perovskite active layer, carrier transport layer, and interface contact layer caused by high-temperature welding above 200°C, thus ensuring the photoelectric performance of the solar cell. Furthermore, a specific stacking sequence of high-temperature cloth, encapsulation cover layer, encapsulation film layer, solder ribbon, and solar cell is employed, along with a fixture featuring grooves and limiting slots, to achieve precise solder ribbon positioning. This prevents positional shifts and stress concentration during the encapsulation process, improving electrode lead-out accuracy and structural uniformity. Moreover, the lamination process completes electrode connection and encapsulation protection in one step, significantly shortening interface exposure time and reducing process turnover.
[0026] Specifically, the encapsulation cover layer is one or more of polyimide (PI) film, polyethylene terephthalate (PET) film, and ethylene-tetrafluoroethylene copolymer (ETFE) film.
[0027] Specifically, the encapsulating film layer is one or more of ethylene-vinyl acetate copolymer (EVA) film, polyolefin elastomer (POE) film, and thermoplastic polyolefin (TPO) film.
[0028] Specifically, the high-temperature cloth is polytetrafluoroethylene coated glass fiber cloth.
[0029] It should be noted that during the lamination process, the perovskite solar cell encapsulation structure is quite sensitive to local pressure, surface indentations, and interfacial stress. If Teflon (polytetrafluoroethylene) is used as the high-temperature fabric for lamination, its fabric texture can easily transfer to the surface of the encapsulation structure during the lamination process, thus forming fabric textures, indentations, or local thickness differences on the encapsulation surface, which in turn affects the encapsulation appearance, interface bonding consistency, and cell reliability.
[0030] This invention uses polytetrafluoroethylene-coated glass fiber cloth as a high-temperature cloth. During the lamination process, it buffers the local pressure difference between the elastic pressing components of the laminator and the encapsulation structure, reducing the risk of texture transfer, local indentation and stress concentration, thereby improving the surface flatness of the encapsulation structure, the consistency of interface bonding and the reliability after thermal shock.
[0031] Specifically, the fixture is made of metal.
[0032] Preferably, the fixture is made of aluminum alloy or stainless steel.
[0033] It should be noted that the metal fixture has high thermal conductivity, which enables rapid heat equalization and uniform temperature transfer during the lamination process, while providing stable mechanical support to improve the consistency of solder melting and the reliability of battery cell packaging during low-temperature welding.
[0034] The fixture includes a fixture body with a groove at the center of the body for accommodating the packaging structure. A limiting groove is formed on the body and communicates with the groove. The limiting groove is used to accommodate, position and guide the solder strip, so that the solder strip maintains a predetermined direction and position during the lamination process and reduces local pressure concentration caused by solder strip protrusion. The number of limiting grooves is determined according to the number of solder strips and is evenly distributed.
[0035] Specifically, the number of positive electrode solder strips is 2-4, and the number of negative electrode solder strips is 2-4.
[0036] Preferably, the number of positive electrode solder strips is 2 and the number of negative electrode solder strips is 2.
[0037] It should be noted that the positive electrode of the perovskite solar cell adopts a peripheral busbar structure (existing structure), where the current is collected in the peripheral electrode area of the cell. When using a single solder strip, the current needs to be transmitted along the peripheral electrode to a single lead-out position, which easily leads to significant lateral resistance loss and uneven current collection. Using two solder strips, the two strips are connected to different positions on the peripheral electrode, allowing the current to flow out simultaneously from two areas, reducing the current load and contact resistance at a single lead-out point. Using four solder strips does not significantly improve the electrical performance compared to using two positive electrode solder strips, but it increases the amount of material used, the number of connection processes, and the number of fixture limiting structures. Therefore, using two solder strips is preferred.
[0038] For the negative electrode of the solar cell (opposite to the positive electrode), using a single solder strip concentrates the current at a single lead-out point, easily leading to increased local contact resistance and mechanical stress. Using two solder strips improves the uniformity of current collection on the back side and the reliability of the connection. Using three or four solder strips does not show a significant improvement in device performance compared to using two solder strips, but increases the amount of solder strips used, assembly complexity, and short-circuit risk. Therefore, using two solder strips is preferred.
[0039] The positive electrode solder strip is located at the edge of the solar cell and is arranged parallel to each other. The negative electrode solder strip is located on the opposite side of the positive electrode solder strip and is arranged parallel to it, with the negative electrode solder strips evenly distributed.
[0040] It should be noted that in this invention, the metal fixture is also used to improve the thickness uniformity during the flexible packaging lamination process. Because the packaging structure is easily affected by uneven local pressure distribution of the elastic pressing components during direct lamination, the degree of compression varies in different areas of the packaging layer. Measurements using the five-point method show that without the fixture, the thickness of the packaging structure at the four corners is approximately 2.0 mm, and the thickness in the center is approximately 2.2 mm, indicating that there is a phenomenon of greater pressure at the four corners and less pressure at the center during lamination, resulting in uneven packaging thickness distribution.
[0041] By employing the metal fixture described in this invention, the fixture can provide support, positioning, and pressure buffering for the battery cells and encapsulation layer during the lamination process, transforming the lamination pressure from a localized concentrated effect to a more uniform one. Measurements using the five-point method showed that after adding the metal fixture, the thickness of the encapsulation structure at the four corners and the center area was approximately 2.2 mm, indicating a more consistent thickness distribution in the encapsulation layer.
[0042] Therefore, the fixture can reduce the risk of mechanical damage to the edges, corners, electrodes and encapsulation layers of the solar cell caused by excessive local pressure during the encapsulation process. On the other hand, it can improve the uniformity of lamination pressure distribution and the consistency of encapsulation thickness, thereby improving the encapsulation reliability and process stability of perovskite solar cells.
[0043] The laminator includes an elastic pressing component made of silicone rubber; during the lamination process, the elastic pressing component contacts the upper surface of the fixture and undergoes elastic deformation under vacuum and pressure conditions to apply flexible pressure to the encapsulation structure within the fixture groove.
[0044] It should be noted that in the lamination process of the present invention, a fixture containing the encapsulation structure needs to be placed into the laminator, and then the elastic pressing component is attached to the upper surface of the fixture. The elastic pressing component is made of elastic material and deforms during lamination, thereby applying flexible pressure to the encapsulation structure, thereby achieving interconnection and encapsulation at the same time.
[0045] Compared to the direct pressure applied by rigid pressing components, the present invention uses elastic pressing components that can better adapt to the slight thickness differences in the packaging structure. In conjunction with the fixture and high-temperature cloth, it can achieve uniform transmission of temperature and pressure fields, thereby improving the packaging consistency and cell reliability during the low-temperature sealing process.
[0046] Specifically, the thickness of the solder layer is 500~1000 nm; the thickness of the silver foil is 20~50 μm.
[0047] It should be noted that, in this invention, to improve the interfacial contact stability between the Ag foil and the battery cell electrode, and to reduce the contact resistance during the lamination process, a solder layer is formed on the surface of the Ag foil. The thickness of this solder layer is controlled within 500~1000 nm. This range ensures the formation of a continuous and uniform covering layer on the Ag foil surface, and also helps to improve the wetting consistency between the solder and the Ag foil, thereby ensuring the reliability and electrical stability of subsequent lamination welding.
[0048] When the solder layer thickness is less than 500 nm, local discontinuities in coverage and insufficient contact area occur, leading to decreased solder strength and contact resistance stability. When the solder layer thickness exceeds 1000 nm, the increased solder usage introduces increased internal stress, local buildup, and a higher risk of reflow overflow and edge short circuits. Therefore, controlling the solder layer thickness within the range of 500–1000 nm is beneficial for balancing solder layer continuity, thickness uniformity, soldering reliability, and packaging safety.
[0049] For example, the thickness of the solder layer can be 500nm, 510nm, 520nm, 530nm, 540nm, 550nm, 560nm, 570nm, 580nm, 590nm, 600nm, 610nm, 620nm, 630nm, 640nm, 650nm, 660nm, 670nm, 680nm, 690nm, 700nm, 710nm, 720nm, 730nm, 7... 40nm, 750nm, 760nm, 770nm, 780nm, 790nm, 800nm, 810nm, 820nm, 830nm, 840nm, 850nm, 860nm, 870nm, 880nm, 890nm, 900nm, 910nm, 920nm, 930nm, 940nm, 950nm, 960nm, 970nm, 980nm, 990nm, or 1000nm.
[0050] In this invention, the thickness of the silver foil is set to 20~50μm. This thickness range provides sufficient mechanical strength and conductive cross-sectional area to ensure current collection and transmission efficiency, while also possessing good flexibility and processability, facilitating bonding with solder layers and subsequent lamination and encapsulation operations. At the same time, it avoids increased stress and material waste caused by excessive foil thickness.
[0051] For example, the thickness of the silver foil is 20μm, 25μm, 30μm, 35μm, 40μm, 45μm or 50μm.
[0052] Preferably, the thickness of the silver foil is 30~35μm.
[0053] Specifically, the raw material for preparing the solder layer is Sn-Bi-based solder.
[0054] Preferably, in the Sn-Bi based solder, the mass percentage of Sn is 30~60 wt% and the mass percentage of Bi is 40~70 wt%.
[0055] It should be noted that the Sn-Bi-based low-temperature solder was chosen as the solder layer material in this invention mainly because the Sn-Bi system is a typical low-melting-point lead-free solder system. Its eutectic or near-eutectic composition has a melting temperature that is significantly lower than that of conventional lead-free solders such as Sn-Ag-Cu, which can reduce the heat input during the sealing process and is suitable for the requirements of perovskite solar cells for low-temperature packaging and low-temperature interconnection processes.
[0056] Perovskite solar cells are highly sensitive to lamination temperature and heat exposure time. High-temperature, long-term lamination can easily lead to interface degradation, increased series resistance, and decreased Voc or FF. Therefore, by pre-plating a Sn-Bi-based low-temperature solder layer on the silver foil surface, the solder layer can soften, partially melt, diffuse at the interface, or wet and spread under the combined effects of lamination temperature, vacuum negative pressure, and external pressure, thereby forming a stable metal connection interface between the silver foil and the solar cell electrodes.
[0057] Furthermore, controlling the mass percentage of Sn to 30-60 wt% and the mass percentage of Bi to 40-70 wt% achieves a balance between low-temperature soldering compatibility, wetting and spreading properties, interfacial bonding strength, and thermal cycling reliability. Within the above composition range, the solder layer can form a eutectic, near-eutectic, or refined Sn / Bi two-phase structure, which is beneficial for improving the contact stability between the solder layer and the silver foil and the cell electrodes.
[0058] If the Bi content is too high, the weld interface becomes more brittle, making it prone to microcracks or increased contact resistance after thermal shock. If the Sn content is too high, the solder liquidus temperature rises, which is detrimental to low-temperature lamination sealing and may increase the risk of thermal damage to perovskite solar cells. Therefore, using Sn-Bi-based solder to prepare the pre-plated solder layer is beneficial for achieving low-temperature interconnection and encapsulation integration of perovskite solar cells.
[0059] Specifically, the Sn-Bi-based solder also contains modifying elements, which are one or more of Ag, In, Sb, and Cu.
[0060] Preferably, the amount of the modified element added accounts for 0.1 to 10 wt% of the Sn-Bi-based solder.
[0061] It should be noted that the Sn-Bi-based low-temperature solder was chosen as the solder layer material in this invention mainly because the Sn-Bi system is a typical low-melting-point lead-free solder system. Its eutectic or near-eutectic composition has a melting temperature that is significantly lower than that of conventional lead-free solders such as Sn-Ag-Cu, which can reduce the heat input during the sealing process and is suitable for the requirements of perovskite solar cells for low-temperature packaging and low-temperature interconnection processes.
[0062] Preferably, the height of the fixture is 1 to 1.5 mm greater than the thickness of the packaging structure.
[0063] Specifically, the lamination parameters include a lamination temperature of 90~100℃ and a lamination pressure of -80~-30kPa.
[0064] Preferably, the lamination pressure is controlled in stages, including a first stage of -80 to -70 kPa with a holding time of 300 to 360 s; a second stage of -70 to -40 kPa with a holding time of 40 to 80 s; and a third stage of -40 to -30 kPa with a holding time of 400 to 480 s.
[0065] It should be noted that in this invention, the lamination parameters include a lamination temperature of 90~100℃ and a lamination pressure of -80~-30kPa. This temperature range matches the melting range of Sn-Bi-based low-temperature solder, ensuring sufficient solder melting and wetting for reliable interconnection while effectively avoiding thermal damage to the perovskite active layer and carrier transport layer caused by traditional high-temperature soldering (above 200℃). Combined with a negative pressure environment (-80~-30kPa), residual gas between the encapsulation material interfaces can be expelled during lamination, reducing bubbles and voids, enhancing the flow and filling effect of the encapsulation film layer, and preventing cell rupture due to excessive high pressure stress, thereby ensuring encapsulation density and module structural integrity.
[0066] For example, the lamination temperature can be 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C, or 100°C.
[0067] For example, the lamination pressure can be -80kPa, -75kPa, -70kPa, -65kPa, -60kPa, -55kPa, -50kPa, -45kPa, -40kPa, -35kPa or -30kPa.
[0068] It should be noted that the lamination process of this invention employs staged pressure control to fully degas, buffer the transition, and achieve low-stress bonding. The first stage is -80 to -70 kPa, with a holding time of 300 to 360 seconds; this is mainly used to expel residual gas from the adhesive layer and interface. The second stage is -70 to -40 kPa, with a holding time of 40 to 80 seconds, used to reduce pressure abrupt changes and prevent wrinkles, springback, and solder strip misalignment in the flexible battery cells. The third stage is -40 to -30 kPa, with a holding time of 400 to 480 seconds. This prolonged holding time promotes adhesive layer leveling, stable interface bonding, and initial curing.
[0069] To more clearly describe the present invention, the following embodiments and comparative examples are provided for further illustration.
[0070] Example 1 An integrated sealing method for perovskite solar cells includes the following steps: S1: A solder layer is pre-plated on the surface of a silver foil with a thickness of 20μm to obtain a solder strip; The solder layer is prepared from Sn-Bi-based solder, wherein the mass percentage of Sn is 60 wt%, the mass percentage of Bi is 40 wt%, and the thickness of the solder layer is 500 nm. S2: Reference Figure 4 The high-temperature cloth, encapsulation cover layer, encapsulation film layer, positive electrode solder ribbon, battery cell, negative electrode solder ribbon, encapsulation film layer, encapsulation cover layer and high-temperature cloth are stacked and assembled in sequence to form an encapsulation structure. The high-temperature cloth is polytetrafluoroethylene coated glass fiber cloth; The encapsulation cover layer is a polyimide (PI) film; The encapsulating film layer is a polyolefin elastomer (POE) film; The positive electrode solder strip is located at the edge of the battery cell, and there are two positive electrode solder strips arranged in parallel. The negative electrode solder strip is located on the opposite side of the positive electrode solder strip and is arranged in parallel with the positive electrode solder strip. The negative electrode solder strip is evenly distributed, and there are two negative electrode solder strips. S3: Reference Figure 1-3 The packaging structure is placed in a fixture, the fixture including a body, a groove for accommodating the packaging structure, and a limiting groove for inserting the solder strip on the body, the limiting groove communicating with the groove. Reference Figure 5 The fixture is made of aluminum alloy, and the height of the fixture is 1 mm greater than the thickness of the packaging structure. S4: Place the fixture inside the laminator, cover the fixture with the elastic pressing component inside the laminator, which is made of silicone rubber, and laminate at 100℃ for 300 s. Control the lamination in stages: first stage -80 kPa for 360 s, second stage -55 kPa for 60 s, and third stage -30 kPa for 480 s to obtain perovskite solar cell.
[0071] Example 2 The preparation process of Example 2 is largely the same as that of Example 1, except that the thickness of the solder layer in Example 2 is 1000 nm.
[0072] Example 3 The preparation process of Example 3 is largely the same as that of Example 1. The difference is that the lamination parameters in Example 3 include a lamination temperature of 90°C, segmented lamination control, a first stage of -70 kPa held for 300 s, a second stage of -65 kPa held for 40 s, and a third stage of -39 kPa held for 400 s.
[0073] Example 4 The preparation process of Example 4 is largely the same as that of Example 1. The difference is that the Sn-Bi-based solder in Example 4 also contains a modifying element, which is Ag, and the amount of the modifying element added accounts for 5.2 wt% of the Sn-Bi-based solder.
[0074] Example 5 The preparation process of Example 5 is largely the same as that of Example 1, except that the number of positive electrode solder strips in Example 5 is 2 and the number of negative electrode solder strips is 4.
[0075] Example 6 The preparation process of Example 6 is largely the same as that of Example 1, except that the number of positive electrode solder strips in Example 6 is 4 and the number of negative electrode solder strips is 2.
[0076] Comparative Example 1 The preparation process of Comparative Example 1 is basically the same as that of Example 1, except that Comparative Example 1 does not use a pre-plated Sn-Bi-based low-temperature solder layer and lamination sealing method for electrode interconnection. Instead, a conventional welding method is used to connect the solder strip to the electrode area of the perovskite solar cell. In the conventional welding method, the temperature setting of the welding tool is 380°C.
[0077] Comparative Example 2 The preparation process of Comparative Example 2 is largely the same as that of Example 1, except that the solder layer thickness in Comparative Example 2 is 100 nm.
[0078] Comparative Example 3 The preparation process of Comparative Example 3 is largely the same as that of Example 1, except that the thickness of the solder layer in Comparative Example 3 is 1500 nm.
[0079] Comparative Example 4 The preparation process of Comparative Example 4 is largely the same as that of Example 1, except that the lamination parameters in Comparative Example 4 include a lamination temperature of 120°C.
[0080] Comparative Example 5 The preparation process of Comparative Example 5 is largely the same as that of Example 1, except that no solder layer is plated on the surface of the silver foil in Comparative Example 5.
[0081] Comparative Example 6 The preparation process of Comparative Example 6 is largely the same as that of Example 1, except that no jig is used in Comparative Example 6, and the encapsulation structure is directly laminated.
[0082] Comparative Example 7 The preparation process of Comparative Example 7 is largely the same as that of Example 1, except that the number of positive electrode solder strips in Comparative Example 7 is 1 and the number of negative electrode solder strips is 2.
[0083] Performance testing Peel strength test, shear strength test, photoelectric conversion efficiency retention rate (PCE retention rate) test after thermal shock test, and photovoltaic electrical performance test before and after packaging were performed on the above embodiments and comparative examples, as shown in Table 1 and Table 2-3.
[0084] In order to eliminate the influence of other factors, the inspection of this invention is divided into two parts: welding and packaging. In the peel strength test, shear strength test, and photoelectric conversion efficiency retention rate test after thermal shock, the performance before and after welding is mainly tested. In the welding process, only the positive electrode solder strip, the battery cell and the negative electrode solder strip are included.
[0085] Table 1. Test results of mechanical strength and welding reliability
[0086] Table 2. Detection results of photovoltaic electrical performance changes in the examples
[0087] Table 3. Comparative photovoltaic electrical performance change test results
[0088] As can be seen from Examples 1-6 and Comparative Examples 1-7, and with reference to Tables 1-3, this invention achieves electrode interconnection at a lower temperature by pre-plating a solder layer on the silver foil surface to form the solder ribbon, combined with a lamination process. This effectively avoids thermal damage to the perovskite active layer, carrier transport layer, and interface contact layer caused by high-temperature welding above 200°C, thus ensuring the photoelectric performance of the solar cell. Furthermore, a specific stacking sequence of high-temperature cloth, encapsulation cover layer, encapsulation film layer, solder ribbon, and solar cell is employed, along with a fixture featuring grooves and limiting slots, to achieve precise solder ribbon positioning and prevent positional displacement and stress concentration during the encapsulation process. The resulting product exhibits high performance after sealing, with a peel strength of 1.70 N·mm. -1 The shear strength is above 8.55 MPa, and the PCE retention rate after thermal shock is above 79.0%.
[0089] Referring to Comparative Example 1, since the perovskite light-absorbing layer, carrier transport layer and electrode interface in the perovskite solar cell are relatively sensitive to high temperature, the local heat input is large during the 380℃ high-temperature welding process, which can easily cause electrode interface degradation, thermal damage to the perovskite layer, increased contact resistance or local failure, resulting in a significant decrease in Voc, FF and PCE of the solar cell after welding.
[0090] Based on Example 1 and Comparative Example 6, measurements using the five-point method show that without a fixture, the thickness of the encapsulation structure at the four corners is approximately 2.0 mm, and the thickness at the center is approximately 2.2 mm. This indicates that during lamination, the corners experience greater pressure, while the center experiences less pressure, resulting in uneven encapsulation thickness distribution. Measurements using the five-point method, with the addition of a metal fixture, show that the thickness of the encapsulation structure at both the four corners and the center is approximately 2.2 mm, indicating a more consistent encapsulation layer thickness distribution.
[0091] Refer to Comparative Example 3 and Figure 6 When the solder layer thickness is greater than 1000 nm, the amount of solder used increases, which leads to increased internal stress in the film layer, local accumulation, backflow overflow and edge short circuit.
[0092] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. An integrated sealing method for perovskite solar cells, characterized in that, Includes the following steps: S1: A solder layer is pre-plated on the surface of silver foil to obtain solder ribbon; S2: The high-temperature cloth, encapsulation cover layer, encapsulation film layer, positive electrode solder ribbon, battery cell, negative electrode solder ribbon, encapsulation film layer, encapsulation cover layer and high-temperature cloth are stacked and assembled in sequence to form an encapsulation structure. S3: Place the packaging structure in a fixture, the fixture including a body, the body having a groove for accommodating the packaging structure, and the body having a limiting groove for inserting the solder strip, the limiting groove communicating with the groove; S4: Place the fixture in the laminator, adjust the lamination parameters and encapsulate to obtain perovskite solar cell wafers.
2. The integrated sealing method for a perovskite solar cell according to claim 1, characterized in that, The thickness of the solder layer is 500~1000 nm; the thickness of the silver foil is 20~50 μm.
3. The integrated sealing method for a perovskite solar cell according to claim 1, characterized in that, The raw material for preparing the solder layer is Sn-Bi-based solder.
4. The integrated sealing method for a perovskite solar cell according to claim 3, characterized in that, In the Sn-Bi based solder, the mass percentage of Sn is 30~60 wt% and the mass percentage of Bi is 40~70 wt%.
5. The integrated sealing method for a perovskite solar cell according to claim 3, characterized in that, The Sn-Bi-based solder also contains modifying elements, which are one or more of Ag, In, Sb, and Cu.
6. The integrated sealing method for a perovskite solar cell according to claim 5, characterized in that, The amount of the modified element added is 0.1 to 10 wt% of the Sn-Bi-based solder.
7. The integrated sealing method for a perovskite solar cell according to claim 1, characterized in that, The height of the fixture is 1 to 1.5 mm greater than the thickness of the packaging structure.
8. The integrated sealing method for a perovskite solar cell according to claim 1, characterized in that, The lamination parameters include a lamination temperature of 90~100℃ and a lamination pressure of -80~-30kPa.
9. The integrated sealing method for a perovskite solar cell according to claim 1, characterized in that, The number of positive electrode solder strips is 2-4, and the number of negative electrode solder strips is 2-4.
10. A perovskite solar cell, characterized in that, It is prepared by the integrated sealing method according to any one of claims 1-9.